Rumph, Stephen. 2004. Beethoven After Napoleon: Political Romanticism in the Late Works. Berkeley and Los Angeles: University of California Press. - Mathew, Nicholas (Current Musicology, 2004)
Beethoven is moving steadily rightwards. After a century or so of criticism that has taken Beethoven’s revolutionary convictions and Enlightenment utopianism for granted, the last decade of Beethoven scholarship has wit-nessed the beginnings of a revisionist trend. Most importantly, several schol-ars have given unprecedented critical attention to the neglected group of compositions that Beethoven composed in the reactionary political climate of the Congress of Vienna-the notorious Wellingtons Sieg foremost among them. 1 With Stephen Rumph’s splendid new book, this revisionist sensibil-ity has finally blossomed into a thesis: Beethoven’s late music, argues Rumph, partakes of the counterrevolutionary politics, nostalgic medievalism, and anti-Enlightenment attitudes of German "political Romanticism." Rumph gives us a Beethoven more at home with Friedrich Schlegel than Immanuel Kant.